Implementation of SKS in the Independent Learning Curriculum in Improving the Quality of Student Output at SMA Muhammadiyah 1 Karanganyar - Sari, Fifi Aswita Mandala; Rohmah, Wafrotur (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to describe: (1) SKS planning and compatibility with the Independent Learning Curriculum; (2) the implementation of the SKS program in the Independent Learning Curriculum in improving the quality of student output; (3) SKS program evaluation; (4) constraints and solutions for implementing SKS in the Independent Learning Curriculum. This type of research is descriptive qualitative research with a case study design. Observation data collection techniques, in-depth interviews and documentation. The object of this study is credits on the independent learning curriculum to improve student quality. The research subjects were the Principal, Deputy Head of Curriculum, SKS management teachers and students. The data validation technique uses source and technique triangulation. Data analysis techniques use the Miles and Huberman analysis model, namely data collection, data reduction, data presentation, and conclusion. The results of the study show (1) the SKS planning carries out various preparations and other supports, as well as the compatibility between the independent curriculum and the SKS; (2) the implementation of the credits in the Independent Curriculum to improve the quality of the output is proven by students who undergo the credits study program being accepted at PTN or PTS; (3) the evaluation of the credit program looks at the achievement of the credit program in serving students; (4) the obstacle in implementing the SKS program lies in the lack of understanding of students, parents, and teacher commitment. The solution is to hold discussions and evaluate things that need to be addressed in the future.